Planners as leaders: finding their comfort zone. Issue 3 (22nd June 2018) - Johnson, Bonnie J.
Abstract : Purpose: Planners are expected to leave leadership to elected officials. Yet, they are often asked to do more. Should planners lead? The purpose of this paper is to examine how leadership is seen in the profession and then outline major theories of leadership and planning. Design/methodology/approach: Using content analysis, the major theories of planning and descriptions of what planners do from professional planning organizations' codes of ethics from around the world are compared. Findings: Results indicate that new ways of thinking about leadership (Group leadership, Servant, Adaptive, Authentic and Followership) can help planners find leadership styles that fit their comfort zones better than old leadership definitions emphasizing heroic individuals. Originality/value: Existing literature regarding leadership in planning indicates that planners must run for office if they are to lead. This examination of planners' codes of ethics and newer theories of leadership indicates they can be leaders and operate well within current ethical boundaries.